Exercise Stroke Volume in Adult Cystic Fibrosis: A Comparison of Acetylene Pulmonary Uptake and Oxygen Pulse. Issue 12 (24th July 2018) - Van Iterson, Erik H; Baker, Sarah E; Wheatley, Courtney M; Morgan, Wayne J; Olson, Thomas P; Snyder, Eric M
Cardiac hemodynamic assessment during cardiopulmonary exercise testing (CPET) is proposed to play an important role in the clinical evaluation of individuals with cystic fibrosis (CF). Cardiac catheterization is not practical for routine clinical CPET. Use of oxygen pulse (O2 pulse) as a noninvasive estimate of stroke volume (SV) has not been validated in CF. This study tested the hypothesis that peak exercise O2 pulse is a valid estimate of SV in CF. Measurements of SV via the acetylene rebreathe technique were acquired at baseline and peak exercise in 17 mild-to-moderate severity adult CF and 25 age-matched healthy adults. We calculatedO 2 p u l s e = V . O 2 H R . Baseline relationships between SV and O2 pulse were significant in CF ( r = .80) and controls ( r = .40), persisting to peak exercise in CF ( r = .63) and controls ( r = .73). The standard error of estimate for O2 pulse-predicted SV with respect to measured SV was similar at baseline (14.1 vs 20.1 mL) and peak exercise (18.2 vs 13.9 mL) for CF and controls, respectively. These data suggest that peak exercise O2 pulse is a valid estimate of SV in CF. The ability to noninvasively estimate SV via O2 pulse during routine clinical CPET can be used to improve test interpretation and advance our understanding of the impact cardiac dysfunction has on exercise intolerance in CF.